2022
DOI: 10.1021/acs.jafc.1c07893
|View full text |Cite
|
Sign up to set email alerts
|

Saponins as Natural Emulsifiers for Nanoemulsions

Abstract: The awareness of sustainability approaches has focused attention on replacing synthetic emulsifiers with natural alternatives when formulating nanoemulsions. In this context, a comprehensive review of the different types of saponins being successfully used to form and stabilize nanoemulsions is presented, highlighting the most common natural sources and biosynthetic routes. Processes for their extraction and purification are also reviewed altogether with the recent advances for their characterization. Concerni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 160 publications
(398 reference statements)
0
13
0
Order By: Relevance
“…CS is a kind of natural, plant-derived surfactant isolated from camellia seed oil press cake. Most are oleanane-type hydrophobic triterpene monodesmosides with three or four hydrophobic saccharide residues attached at C-3 . CS has strong surface activity due to its peculiar molecular structure (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CS is a kind of natural, plant-derived surfactant isolated from camellia seed oil press cake. Most are oleanane-type hydrophobic triterpene monodesmosides with three or four hydrophobic saccharide residues attached at C-3 . CS has strong surface activity due to its peculiar molecular structure (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Most are oleanane-type hydrophobic triterpene monodesmosides with three or four hydrophobic saccharide residues attached at C-3. 30 CS has strong surface activity due to its peculiar molecular structure (Figure 1A). The interfacial properties of emulsifiers play an important role in foaming and stabilizing water-continuous emulsions.…”
Section: Characterization Of Interfacial Properties Ofmentioning
confidence: 99%
“…A recent review (Schreiner et al, 2022) on saponins as natural emulsifiers highlighted saponin-rich extracts as alternatives to Quillaja saponin and other highly pure saponins. These solutions are recognized as more sustainable and low-cost options.…”
Section: Introductionmentioning
confidence: 99%
“…Although Quillaja saponin proved to be an excellent surfactant, there is a current need to identify and apply alternative saponin sources mainly due to questions of sustainability and cost (Schreiner et al, 2022), also preventing the overexploitation of the Quillaja tree (Reichert et al, 2018). Some studies have reported the use of saponins extracted from the Yucca tree ( Yucca schidigera ) (Ralla, Salminen, Tuosto, et al, 2017; Tsibranska et al, 2020), sugar beet ( Beta vulgaris ) (Ralla, Salminen, Edelmann, et al, 2017), oat bran ( Avena sativa L.) (Ralla et al, 2018), tea saponin (Zhu et al, 2019), and argan press cake and shells (Bouhoute et al, 2020; Taarji et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation